Clinical Risk Factors for NonSalvageable Testis in Testicular Torsion Patients - Daryanto, Besut; Indradiputra, I Made Udiyana; Satyagraha, Paksi (International Journal of Psychosocial Rehabilitation, 2020)
This retrospective study was conducted to describe and analyze the clinical risk factors of non salvageable affected testis in pediatric and adult testicular torsion patients in Saiful Anwar Hospital Malang.Orchiectomy and contralateral orchidopexy were performed to 63 patients (90%) due to non-viable affected testis, with the left testis as the most commonly affected (48 patients/68.6%). It was found that symptom onset more than 6 hours was associated to increase the likelihood of non-salvageable testis/orchiectomy (odds ratio/OR 155; 95% confidence interval =11.9-2020.3, p<0.001). Lesser degree of torsion was also associated with likelihood of salvageable testis (OR 0.992; 95% confidence interval=0.985-0.999, p=0.032), with most torsion cases were medially rotated (91.4%). Vertical testicular position during initial examination is associated with less risk of orchiectomy (OR 0.159, 95% confidence interval=0.031-0.812, p=0.034). It was revealed that phren’s test result, and the presence of cremaster reflex during initial examination had no association with surgical outcome, and so did the laboratory result (p>0.05).The duration of symptoms until detorsion was the most important modifiable factor of salvageable testis in testicular torsion patient, hence immediate (<6 hours) detorsion by surgical exploration is recommended. The degree of torsion along with testicular position was affected the likelihood of orchiectomy. Proper health education and direct referral to hospital may reduce this delay for reducing orchiectomy rate in the future.